Intramolecularly Double‐Donor‐Stabilized Stannylene and Its Coordination towards Ag(I) and Au(I) Centers. Issue 15 (19th June 2021) - Chibde, Purva; Raut, Ravindra K.; Kumar, Vikas; Deb, Rahul; Gonnade, Rajesh; Majumdar, Moumita
Abstract: The intramolecularly double‐donor‐stabilized stannylene 1 has been synthesized from the salt‐metathesis reaction between two equivalents of lithium pyridine ene‐amide L1 and SnCl2 . Compound 1 exhibits dipolar behavior when reacted with B(C6 F5 )3 leading to the zwitterionic compound 2 . The reaction of 1 with one equivalent and 0.5 equivalent of AgOTf (OTf=trifluoromethane sulfonate) result in the formation of a stannylene‐AgOTf complex 3 and a homoleptic distannylene‐silver ionic complex 4, respectively. Analogous to complex 4, the gold(I) complex 5 has been synthesized from the reaction between two equivalents of 1 and 0.5 equivalent of AuCl.SMe2 /Me3 SiOTf. Complex 5 is the first example of homoleptic stannylene‐Au(I) ionic complex among the very scarce reports on stannylene‐gold(I) coordination complexes. All compounds have been structurally characterized using single crystal X‐ray crystallography. Solution‐state characterization have been performed using multinuclear NMR techniques. Detailed DFT calculations on the optimized geometries 1 o, 3 o –5 o reveal the change in sp ‐ hybridization on the pyramidal Sn(II) center upon metal coordination and their bonding overlaps. Abstract : An intramolcularly double‐donor‐stabilized stannylene showing enhanced donor ability has been established using pyridine ene‐amide as the supporting ligand. This stannylene not only coordinates to the Ag(I) center, but also shows remarkable coordination to the Au(I) cation giving the first example of an ionic homoleptic distannylene‐gold(I) complex.